(3ebGdI aj QSe GdbWhY GdKdGKIs - (3EHQGgje Hf SfGf Hf KGHJ Hf bQI Hf eQhGf Hf KGHJ, CHh ESMGb GdMqQGfj Ke GdHZOGOj,J (B335 (3g` s ((3GdehUd s)
(3ChdgG (B:s
(3gPg GdCTcGd GdJi fPcQgG gGgfG djS JSdc ajgG GdWQjb GdJiSdcfgG ai GdKdGK YTQg ebGdg s
(3BNQgG (B:s
(3ajUjQ edJbi GdNWhW Ydi GdbWY GdfGbU ceG jHjf ai cJGH (B" (3GdeNQhWGJ (B" s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B42 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B36s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B218 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B89 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs